Effect of game-based learning activities on children’s positive learning and prosocial behaviours - Lu, Chung Chin; Effandi Zakaria (penerbit ukm, 2015)
The purpose of this research is to investigate the effect of game-based learning activities (GBL) on children’s positive learning and prosocial behaviours. Games in this research are referred to a set of games with rules which are adapted or designed by the researcher based on the National Pre-school Standard Curriculum for preschool mathematics education. The games involved the use of cards, game board, and dice. Children played the games in groups. This research used quasi-experimental with non-equivalent control group pre test/post-test research design. The treatment group consisted of 23 preschool children using GBL while the control group consisted of 24 preschool children who use traditional methods of teaching and learning. An independent-samples t-test was conducted to compare the mean score of children’s learning behaviours between treatment and control group. There was a significant difference in the mean scores for treatment group (M = 38.74, SD = 5.5) and control group (M = 23.00, SD = 14.79) conditions; t (45) = -4.795, p = 0.00. Data collected for prosocial behaviour were based on the frequency of occurrence of behaviours that have been identified and presented in the form of graphs. The results showed that the treatment group gained much higher frequency of occurrence in prosocial behaviours compared to the control group. These results suggest that GBL is effective in nurturing children’s positive learning and prosocial behaviours. The research can serve as a guideline especially to rural preschool teachers in applying GBL in their classroom.